Nonattendance in preventive child health examinations associated with increased risk of school‐aged obesity in Denmark - Heuckendorff, Signe; Brund, René Børge Korsgaard; Eggertsen, Charlotte Nørkjær; Thomsen, Janus Laust; Fonager, Kirsten (Acta Paediatrica, 2025)
Aim The aim of this study is to investigate associations between attending routine preventive child health examinations in general practice and the risk of obesity and overweight at age six, focusing on psychosocial risk factors. Methods Data from nationwide Danish registers on 725 926 children born between 2000 and 2012 were analysed. Information on examination attendance and BMI was obtained. Regression analyses assessed the association between examination attendance and obesity or overweight risk. Results Non‐attendance in preventive child health examinations was associated with a risk of obesity of 18%–31% at age six. The highest risk was observed in children of parents with low educational attainment who missed all examinations, a four‐ to five‐fold increase compared to children of parents with high educational attainment who attended all or missed only one exam. A smaller association of one to 2% was found between missing examinations and risk of overweight in the general population. However, children of parents with low educational attainment who did not attend were 8%–9% more likely to have overweight. Conclusion Associations were found between obesity and overweight and not attending preventive child health examinations in general practice. Further research is needed to understand the mechanisms and develop targeted interventions to address health disparities in childhood obesity.